Haunted holidays : twelve months of Kentucky ghosts - Brown, Roberta Simpson, 1939-; Brown, Lonnie E. (University Press of Kentucky, 2015)
"In Haunted Holidays, celebrated storytellers Roberta Simpson Brown and Lonnie E. Brown have assembled a hair-raising collection of paranormal tales for readers of all ages. The stories present many new and spooky characters, including the deceased great aunt who still rocks in her favorite chair on Mother's Day, the young boy who made good on his promise to return a silver dollar on the Fourth of July, and even the ghost who hated Labor Day. In addition to tales of haunting, the Browns reveal many Appalachian legends and their importance to the storytelling tradition, such as the phantom bells who guide the dead to the other side, and a "chime child" born when the clock strikes midnight on Christmas Day, who is rumored to be blessed with the gift of second sight. More than a collection of ghost stories or family legends, Haunted Holidays takes readers on a fireside journey that preserves and promotes oral traditions, revealing the importance of sharing beliefs, traditions, and values with a new generation of listeners."--Publisher's description.